An introduction to conducting responsible and reproducible agricultural research - Sichinga-Ligowe, Ivy; J M Joy, Edward; Manzeke-Kangara, M Grace; Pino, Loreto; Rivero, M Jordana; Devkota Wasti, Mina Kumari; R. Broadley, Martin; Haefele, Stephan M; McGrath, Steve P. (CAB International, 2024)
This article aims to provide researchers with introductory guidance to good practices in the design, conduct and reporting of agricultural research. This narrative review considers issues related to research co-design, ethics and integrity, equity, diversity and inclusion, reproducibility and (meta)data reporting. Aspects for researchers to consider are highlighted, and relevant resources are identified, including academic papers and research funder guidance.